Research Methodologies and Ethical Challenges in Digital Migration Studies 2021
DOI: 10.1007/978-3-030-81226-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Contrapuntal Connectedness: Analysing Relations Between Social Media Data and Ethnography in Digital Migration Studies

Abstract: This chapter presents a rethinking of the relationship between ethnography and so-called big social data as being comparable to those between a sum and its parts (Strathern 1991/2004). Taking cue from Tim Ingold’s one world anthropology (2018) the chapter argues that relations between ethnography and social media data can be established as contrapuntal. That is, the types of material are understood as different, yet fundamentally interconnected. The chapter explores and qualifies this affinity with the aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Elsewhere, they carefully commend that datasets coming from migrant Facebook groups require consent, while collecting migrants' Twitter data would be closer to observing public behavior and therefore less problematic (Mahoney et al, 2022a ; p. 339–340). A similar recommendation comes from Sandberg et al ( 2022a ).…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Elsewhere, they carefully commend that datasets coming from migrant Facebook groups require consent, while collecting migrants' Twitter data would be closer to observing public behavior and therefore less problematic (Mahoney et al, 2022a ; p. 339–340). A similar recommendation comes from Sandberg et al ( 2022a ).…”
Section: Introductionsupporting
confidence: 56%
“…Finally, although the procedures described here could be interpreted as in a legally gray zone, no involved parts were harmed in this data collection and analysis procedure. Therefore, such research is defensible when an appropriate research question is addressed and standards are followed, as researchers have already been doing (Mahoney et al, 2022a ; Sandberg et al, 2022a ).…”
Section: Final Determinationmentioning
confidence: 99%
“…It is equally exciting when tensions are found that reveal contrapuntal connectedness [23]. Sandberg et al [23] cite Ingersol 16] and Said [24] in demonstrating how comparing various data sources and disparate trends within the data function like a complicated musical score-the data do not function in opposition to each other; they can exist as harmonically distant but still interconnected (p. 53). Quantitative findings, as will be seen here, offer new ways to understand, question, and contextualize the qualitative data.…”
Section: Mixed Methods and Productive Tensionsmentioning
confidence: 99%
“…Informed consent is a core principle of this type of ethical process and has been the subject of various strategies and recommendations that highlight the importance of ensuring that vulnerable participants understand the implications of being involved in a research project (European Commission, 2020). If such principles and associated guidance are frequently discussed in relation to qualitative and traditional research methods (European Commission, 2020), these are not readily applicable to social media analytics and the specific ethical challenges they raise (Sandberg et al, 2022). Indeed, when analysing big data from social media platforms, it is not always possible or feasible to seek the data subjects’ explicit consent to the use of their data, meaning that individuals may not be aware of who uses their data and how it is used (Fiesler and Proferes, 2018).…”
Section: Ethics In Migration and Social Media Researchmentioning
confidence: 99%